The role of catecholamines in preschool children in the neurotic development pathogenesis - Oleksyuk, Z.Ya.; Dakhbay, B.D.; Danilenko, M. (Fundamental and Experimental Biology, 2018)
The clinic of neurosis is diverse, but common symptoms are fears and anxiety, depression, mood swings, obsessions and other manifestations. In addition, it is believed that mental trauma, causing an emotion of fear or fright affect, can lead not only to cardiovascular, but alsoto various other violations of the functions of internal organs. All higher forms of human behavior are associated with the vital activity of nerve cells synthesizing catecholamines. Neurons use catecholamines as neurotransmitters (mediators) that carry the nerve impulse. From the activity of synthesis and isolation of catecholamines, such complex processes as the memorization and reproduction of information, aggressive reaction, mood, emotionality, etc. depend. The highest level of catecholamines (per unit of body weight) in children. The article evaluates the results of excretion of catecholamines in preschool children with different mental status. The study has found differences in their metabolism in children with neurotic manifestations and healthy. Biochemical indicators of biological fluids reflect the characteristics of the state of biochemical systems of the brain, in particular, they are indicators of the activity of the sympathetic-adrenal system. This suggests that the evaluation of excretion of catecholamines can be used as a diagnostic method for this disorder.